Letter to the editor on “Asymptomatic infection by SARS 2 coronavirus: invisible but invincible" by Nikolai et al. 2020 (2020)
We send this letter regarding the article "Asymptomatic infection by SARS 2 coronavirus: invisible but invincible" published in the International Journal of Infectious Diseases (Nikolai et al. 2020). The review was interesting in many aspects, particularly those related to the lack of a widely accepted definition of asymptomatic carriers and presymptomatic patients, as well as the need to include these types of cases in regular epidemiological surveillance.